A study on consumers’ awareness and satisfaction on Agromas products / Dol Hadi Mili - Mili, Dol Hadi (2003)
FAMA, Federal Agricultural Marketing Authority of Malaysia, was established on 30th September 1965. It is a statutory body under the jurisdiction of the ministry of Agricultural of Malaysia to supervise, coordinate and improve the marketing of country agricultural products.